COCAINE VERSUS FOOD CHOICE PROCEDURE IN RATS: ENVIRONMENTAL MANIPULATIONS AND EFFECTS OF AMPHETAMINE12. Issue 2 (14th January 2013) - Thomsen, Morgane; Barrett, Andrew C.; Negus, S. Stevens; Caine, S. Barak
Abstract We have adapted a nonhuman primate model of cocaine versus food choice to the rat species. To evaluate the procedure, we tested cocaine versus food choice under a variety of environmental manipulations as well as pharmacological pretreatments. Complete cocaine‐choice dose‐effect curves (0–1.0 mg/kg/infusion) were obtained for each condition under concurrent fixed ratio schedules of reinforcement. Percentage of responding emitted on the cocaine‐reinforced lever was not affected significantly by removal of cocaine‐associated visual or auditory cues, but it was decreased after removal of response‐contingent or response‐independent cocaine infusions. Cocaine choice was sensitive to the magnitude and fixed ratio requirement of both the cocaine and food reinforcers. We also tested the effects of acute (0.32, 0.56, 1.0, 1.8 mg/kg) and chronic (0.1, 0.32 mg/kg/hr) d‐amphetamine treatment on cocaine choice. Acute and chronic d‐amphetamine had opposite effects, with acute increasing and chronic decreasing cocaine choice, similar to observations in humans and in nonhuman primates. The results suggest feasibility and utility of the choice procedure in rats and support its comparability to similar procedures used in humans and monkeys.